2012
DOI: 10.1155/2012/197540
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Surface Area across the Allograft-Host Junction Site Using Conventional and Navigated Osteotomy Technique

Abstract: Bulk allograft reconstruction plays an important role in limb-salvage surgery; however, non-union has been reported in up to 27% of cases. The purpose of this study is to quantify average surface contact areas across simulated intraoperative osteotomies using both free-hand and computer-assisted navigation techniques. Pressure-sensitive paper was positioned between two cut ends of a validated composite sawbone and compression was applied using an eight-hole large fragment dynamic compression plate. Thirty-two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…They describe a non-union rate of 6%, which compares well to the literature published on non-CATS allograft surgery [72]. This may well be related to an improvement in the contact area between the native bone and allograft using navigated pre-planned cuts versus freehand osteotomies, which has been suggested previously [73].…”
Section: Appendicular Skeletonsupporting
confidence: 75%
“…They describe a non-union rate of 6%, which compares well to the literature published on non-CATS allograft surgery [72]. This may well be related to an improvement in the contact area between the native bone and allograft using navigated pre-planned cuts versus freehand osteotomies, which has been suggested previously [73].…”
Section: Appendicular Skeletonsupporting
confidence: 75%
“…First, virtually selecting the appropriate donor bone with the use of a virtual bone bank will provide the surgeon with the most suitable graft to obtain the best anatomical fitting [13]. Second, the allograft can be precisely cut using intraoperative navigation techniques to perform osteotomies with extreme accuracy with what was previously virtually planned [9].…”
Section: Discussionmentioning
confidence: 99%
“…Virtual planning of the cuts and intraoperative navigation during the procedure may increase accuracy of the fitting of the host-donor junctions and application of the preplanned fixation. Lall et al [9] analyzed 32 samples to quantify average surface contact areas across simulated intraoperative osteotomies using both freehand and computer-assisted navigation techniques. Mean contact area using the freehand osteotomy technique was equal to 0.21 square inches.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 A study by Lall and colleagues demonstrated better fit and increased contact between allograft implant and resection planes during reconstructive surgery with the use of navigation technology. 49 This could potentially result in improved bone healing and decreased non-union rates, which are reported to be as high as 27% in bulk allograft reconstruction.…”
Section: Navigation Technology and Musculoskeletal Oncologymentioning
confidence: 99%